IMPLEMENTASI JARINGAN VPN BERBASIS IP-MPLS PADA PT. MHE DEMAG INDONESIA - Suryanto Suryanto; Sari Dewi (Paradigma, 2013)
The research objective is to design and build a network linking the headquarters with a branchoffice in PT. MHE DEMAG Indonesia, so change data going to run safely and smoothly with thehope it can improve network performance and company performance in support of businessprocesses. To meet these needs may use a technology called Virtual Private Network (VPN). IPVPNMPLS has a better degree of flexibility compared to leased lines, frame relay, and ATM, andalso offer a cheaper solution. VPN technology can be formed with a facility that can tunnel acrossthe MPLS network. The tunnel facility can build a site to site connection lines are virtual and havea pretty good level of security because it can only be accessed by users who are on the wrong site(private connection). IP MPLS is a data communication services in the form of dedicated leasedIP-based channel with its main advantage is able to provide any services to any connection.MPLS-based IP VPN technology can provide services include: Intranet, Extranet, and RemoteDial. In addition, this technology also has some clappers like: Multiservices Platform,Provisioning Scalability, Cost Saving Opportunity and Security. This study discusses theimplementation of IP-based MPLS VPN used on PT. MHE DEMAG Indonesia and the authorsconducted experiments with simulations. Simulation program used is GNS3 and Cisco IOS.Simulation test results showed IP-MPLS VPN works. VPN-MPLS IP VPN is able to separate theone with the other so as to improve and guarantee the safety factor between head office andbranch offices.Keywords: Internet Protocol, Komunikasi data, MPLS, VPN